Synthesis and base-pairing properties of pyrazine nucleic acids. (2nd June 2020) - Gately, Maura; Wong, Sarah; Peoples, Jennifer; Galamay, Davin; Delgado, Guillermo; Weber, Arthur L.; Campbell, Tammy
Abstract: The diversity of backbone modifications in the study of primitive informational polymers is partly limited by the plausible formation of their prebiotic starting components. In this paper, we synthesize pyrazine nucleic acid, an acyclic polymer, with the nucleoside derivable from a prebiotic one-pot synthesis containing alanine amide and D -ribose. Pyrazine nucleic acid (PzNA) which has a backbone structurally similar to glycerol nucleic acid (GNA), contain pyrazine derived nucleosides as informational elements that may exhibit base pairing properties similar to the pyrimidines present in RNA. [ 1 ] We found that insertion of pyrazinone nucleotides into DNA oligonucleotide sequences is not well-tolerated, and that homogenous sequences of PzNA are unable to form duplexes with RNA or DNA. Reasons for our results may be attributed to the pyrazine-2-one moiety, which is purposed to be a thymine analog, but has a lower p K a (p K a ∼ 8.5) than thymine and uracil. Additionally, we discovered an "apparent" regioselective protection of pyrazine-2-one derivatives in the presence of a secondary hydroxyl group that proved crucial in the preparation of the pyrazine-2-one phosphoramidite. The regioselectivity observed is proposed to be of general interest in the context of heterocyclic chemistry. In the larger context of origins of life studies, it points to the importance of keto-enol preferences of the canonical nucleobases versus pyrazine heterocycles in functioning as recognition elements.